Seasonal variation in added sugar or sugar sweetened beverage intake in Alaska native communities: an exploratory study - Courtney Hill; Sarah H. Nash; Andrea Bersamin; Scarlett E. Hopkins; Bert B. Boyer; Diane M. O’Brien; Donald L. Chi (International Journal of Circumpolar Health, 2021)
Excess added sugar intake contributes to tooth decay risk in Alaska Native communities. The goal of this exploratory study was to determine if there is seasonal variation in total added sugar intake or in the leading sources of added sugars in a Yup’ik population. Data were collected in spring and winter from 2008-2010 using self-reported intake data measured by 24-hour recall and by hair biomarker (carbon and nitrogen stable isotope). Seventy Yup’ik participants ages 14–70 years were recruited from two communities and data were collected twice from a subset of 38 participants. Self-reported added sugar intake (g/day), biomarker-predicted added sugar intake (g/day), and leading sources of added sugar were calculated. Seasonal variation was evaluated using a paired sample t-test. Total added sugar intake was 93.6 g/day and did not significantly differ by season. Sodas and other sugar-sweetened beverages (e.g. Tang, Kool-Aid) were the leading sources and added sugar from these sources did not significantly differ by season (p=.54 and p=.89, respectively). No seasonal variation in added sugar intake was detected by either self-report or biomarker. Dietary interventions that reduce intake of added sugars have the potential to reduce tooth decay in Yup’ik communities.